The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Fracture analysis of the lithium-bearing Cligga Head granite: Impacts on critical mineral mobilisation and fluid flow - Andrew J.M. Evans; Natalie J.C. Farrell; David A. Neave; Margaret E. Hartley; David Healy; John P. Waters; Tara R. McElhinney; Joshua J. Shea; Nico Bigaroni; Simon A. Hunt (Journal of Structural Geology, 2025)

A pilot study investigating feasibility of mainstreaming germline BRCA1 and BRCA2 testing in high-risk patients with breast and/or ovarian cancer in three tertiary Cancer Centres in Ireland - Terri Patricia McVeigh; Karl J. Sweeney; Donal J. Brennan; Una M. McVeigh; Simon Ward; Ann Strydom; Sheila Seal; Katherine Astbury; Paul Donnellan; Joanne Higgins; Maccon Keane; Michael J. Kerin; et al. (Familial Cancer, 2023)

Artificial aeration of an overloaded constructed wetland improves hypoxia but does not ameliorate high nitrogen loads - Danielle J. Allen; Mark Farrell; Jianyin Huang; Simon Plush; Luke M. Mosley (Journal of Environmental Management, 2023)

Evidence for three distinct climate change audience segments with varying belief-updating tendencies: implications for climate change communication - Matthew Andreotta; Fabio Boschetti; Simon Farrell; Cécile Paris; Iain Walker; Mark Hurlstone (Climatic Change, 2022)
Mounting evidence suggests members of the general public are not homogeneous in their receptivity to climate science information. Studies segmenting climate change views typically deploy a top-down approach, whereby concepts salient in scientific literature determine the number and nature of segments. In contrast, in two studies using Australian citizens, we used a bottom-up approach, in which segments were determined from perceptions of climate change concepts derived from citizen social media discourse. In Study 1, we identified three segments of the Australian public (Acceptors, Fencesitters, and Sceptics) and their psychological characteristics. We find segments differ in climate change concern and scepticism, mental models of climate, political ideology, and worldviews. In Study 2, we examined whether reception to scientific information differed across segments using a belief-updating task. Participants reported their beliefs concerning the causes of climate change, the likelihood climate change will have specific impacts, and the effectiveness of Australia’s mitigation policy. Next, participants were provided with the actual scientific estimates for each event and asked to provide new estimates. We find significant heterogeneity in the belief-updating tendencies of the three segments that can be understood with reference to their different psychological characteristics. Our results suggest tailored scientific communications informed by the psychological profiles of different segments may be more effective than a “one-size-fits-all” approach. Using our novel audience segmentation analysis, we provide some practical suggestions regarding how communication strategies can be improved by accounting for segments’ characteristics.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A Continental-Scale Validation of Ecosystem Service Models - Simon Willcock; Danny A. P. Hooftman; Stefano Balbi; Ryan Blanchard; Terence P. Dawson; Patrick J. O’Farrell; Thomas Hickler; Malcolm D. Hudson; Mats Lindeskog; Javier Martinez-Lopez; Mark Mulligan; Belinda Reyers; et al. (Ecosystems, 2019)